Development of Physics Co-Curricular Worksheets Based on Mabbulo Sipeppa Local Wisdom to Support Deep Learning - Dedy Kurniawan; M. Agus Martawijaya; Khaeruddin (PT FORMOSA CENDEKIA GLOBAL, 2026)
The integration of local wisdom into physics co-curricular activities is important to support deep learning and strengthen students’ critical reasoning skills. This study aims to develop and evaluate a physics co-curricular worksheet based on mabbulo sipeppa local wisdom to support critical reasoning in deep learning. The research employed a Research and Development approach using the Borg & Gall procedure integrated with the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through interviews, questionnaires, and tests. The developed worksheet was evaluated in terms of validity, practicality, and effectiveness. The results showed that the worksheet achieved a construct validity index of 1.00, indicating a valid category. The feasibility assessment reached 85.42% from media experts and 85.83% from material experts, both categorized as highly feasible. Practicality results showed positive responses from teachers (97%) and students (98%), indicating that the worksheet is practical for implementation. The effectiveness test produced an average N-gain score of 0.6 (moderate category) with an effectiveness percentage of 60%, interpreted as moderately effective. These findings indicate that the developed worksheet is valid, practical, and sufficiently effective in supporting students’ critical reasoning within the context of deep learning through the integration of mabbulo sipeppa local wisdom.